Evaluation management strategies for Layang Reservoir using fuzzy composite programming - 439752 Chang, Wei Chung (Skudai : Universiti Teknologi Malaysia, 2005)
Project Paper (Sarjana Muda Kejuruteraan Awam) - Universiti Teknologi Malaysia, 2005